Hepatitis C‐positive donor to negative recipient kidney transplantation: A real‐world experience. Issue 3 (9th January 2021) - Jandovitz, Nicholas; Nair, Vinay; Grodstein, Elliot; Molmenti, Ernesto; Fahmy, Ahmed; Abate, Mersema; Bhaskaran, Madhu; Teperman, Lewis
Abstract: Background: Several studies have shown that transplanting a hepatitis C virus (HCV)‐negative recipients with a HCV‐positive donor is feasible in a research setting. In February 2018, we began transplanting HCV‐negative recipients with HCV‐positive donors as standard of care. Methods: All patients, except those with previously cured HCV and those with cirrhosis, were consented for HCV NAT‐positive donor kidneys. After transplantation, patients were tested for HCV RNA until viremic. A direct‐acting antiviral (DAA) agent was prescribed based on genotype and insurance approval. Sustained virologic response (SVR) at weeks 4 and 12 was recorded. Renal function and death censored graft survival at 1 year were evaluated and compared to recipients of HCV NAT‐negative kidneys. Results: A total of 25 HCV NAT‐positive donor kidney transplants from February to October 2018 were performed. All patients received basiliximab and maintained with tacrolimus, mycophenolate mofetil, and prednisone. Median time from viremia to start of DAA was 13 (8‐22) days. The most common genotype was 1a (60%), followed by 3a (28%). The most commonly prescribed DAA was ledipasvir/sofosbuvir (56%), followed by velpatasvir/sofosbuvir (32%), and then glecaprevir/pibrentasvir (12%). All patients achieved initial SVR12, except one. One patient had a mixed‐genotype infection requiring retreatment to achieve SVR12. Death censored graft survival was 96%. Recipients of HCV NAT‐positive organs compared to HCV NAT‐negative organs received younger donors (mean 35 ± 8.9 vs 45.1 ± 15.7 years; P < .01) and spent less time on the waitlist (median 479 (93‐582) vs 1808 (567‐2263) days; P = .02). Conclusion: HCV NAT‐negative recipients can be safely and successfully transplanted with HCV NAT‐positive donor kidneys outside of a research protocol. Access to DAA and timely administration of therapy is important and an insurance approval process within the transplant center can be beneficial to patients. A case of mixed‐genotype infection was presented, and although not as common, can be successfully treated. HCV organs can expand the organ pool and should no longer be considered experimental. The use of these organs in HCV‐negative recipient's decreases waiting time, have excellent outcomes, and should be considered standard of care.